PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA INDOMARET TAMAN MEDITERANIA - Nuraini, Nanik; Oktavia, Yunisa (SCIENTIA JOURNAL, 2020)
Economic growth has brought progress to the business world. The number of retail companies in Batam City has caused competition among competitors. The purpose of this study was to determine the effect of service quality and promotion on purchasing decisions. The method used in this research is quantitative research methods. The population in this study was consumers of Indomaret Taman Mediterania Batam, with a total of 100 respondents. Data collection techniques using purposive sampling. Data collection methods by distributing questionnaires. Data were processed using SPSS version 25. Using the classic assumption test analysis techniques, in the form of normality tests, heteroscedasticity tests, multicollinearity tests, T tests, F tests and analysis of the coefficient of determination (R2 ). F test results show that service quality and promotion simultaneously influence purchasing decisions. This is proven by T-Test = 23,943 > F = 3.93. And as evidenced by the Test F = 23,943 > F = 3.93 significant effect on purchasing decisions. The results of this study indicate that Service Quality has a positive and significant effect on Purchasing Decisions. Quality and Promotion of Services simultaneously have a significant effect on Purchasing Decisions. Service Quality has a positive and significant impact on Purchasing Decisions. Keywords: Service Quality, Promotion, Purchase Decision